2012
DOI: 10.1159/000345151
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes Express IL-6 and Lipocalin 2/ Neutrophil Gelatinase-Associated Lipocalin in Lipopolysaccharide-Induced Acute Glomerular Injury

Abstract: Background/Aims: Acute kidney injury (AKI) contributes to significant morbidity and mortality in the intensive care unit (ICU). Plasma levels of interleukin (IL)-6 predict the development of AKI and are associated with higher mortality in ICU patients with AKI. Most studies in AKI have focused on the tubulo-interstitium, despite evidence of glomerular involvement. In the following study, our goals were to investigate the expression of IL-6 and its downstream mediators in septic-induced AKI. Methods: Podocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 140 publications
1
26
1
1
Order By: Relevance
“…The role of gp130 signaling in podocytes is not well understood and has only been studied in the role of IL-6 signaling in this cell type (Kim and Park, 2013). In rat podocytes, IL-6 evokes an increase in expression of apoptotic markers that coincides with stimulation of p53 expression (Kim and Park, 2013), along with expression of inflammatory markers (Lee et al, 2012). …”
mentioning
confidence: 99%
“…The role of gp130 signaling in podocytes is not well understood and has only been studied in the role of IL-6 signaling in this cell type (Kim and Park, 2013). In rat podocytes, IL-6 evokes an increase in expression of apoptotic markers that coincides with stimulation of p53 expression (Kim and Park, 2013), along with expression of inflammatory markers (Lee et al, 2012). …”
mentioning
confidence: 99%
“…Клетки ме-зангия, а также макрофаги, лимфоциты и эндотелиальные клетки могут секретировать ИЛ-6 в ответ на воздействие факторов воспаления [13]. Однако в биоптатах почек па-циентов со значительной мочевой экскрецией ИЛ-6 не находят мононуклеарных и лимфоцитарных инфильтра-тов, что предполагает наличие и другого источника этого фактора [14]. Полагают, что таким источником ИЛ-6 мо-гут быть ПД.…”
Section: рис 2 оценка выраженности подоцитопении по экс-прессии Wt-unclassified
“…11 To localize the site of Lcn2/Ngal production, we performed in situ RNA hybridization and observed glomerular expression of Lcn2/ Ngal in the diabetic WT and TRB3 2/2 mice (Supplemental Figure 2). , and studies have shown that in certain cell types TRB3 inhibits the phosphorylation of AKT.…”
Section: Absence Of Trb3 Augments Er Stress In Diabetic Micementioning
confidence: 99%
“…11,76 Primary podocytes were propagated from kidneys from 6-to 10-week-old WT and TRB3 2/2 mice with Dynabeads (Life Technologies, Grand Island, NY) as we have previously reported. Passage 2 cells were used, and for validation they were grown on cover slips and stained with antisynaptopodin antibody (clone G1D4; Fitzgerald Industries, Acton, MA).…”
Section: Cultured Cellsmentioning
confidence: 99%